2021
DOI: 10.7759/cureus.13969
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Optic Atrophy in a Young Patient With Chronic Anaemia Secondary to End-Stage Renal Disease

Abstract: End-stage renal disease (ESRD) is associated with a number of serious complications, including increased cardiovascular disease, anaemia and metabolic bone disease. Optic atrophy secondary to chronic anaemia in ESRD is rare. We report a case of bilateral optic atrophy in a young patient with chronic anaemia secondary to ESRD. A 23-year-old lady with ESRD, presented with progressive blurring of vision in her left eye for a period of six months. Visual acuity in the left eye was counting finger and the right eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…The most common is chronic anemia in people with renal impairment leading to anemia that nourishes the optic nerve head. 9 , 18 In addition, due to vascular system disorders, renin-angiotensin damages the ganglion cell layer, the nerve fiber layer. 19 In the post-transplant stage, optic nerve atrophy is thought to be associated with post-transplant infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common is chronic anemia in people with renal impairment leading to anemia that nourishes the optic nerve head. 9 , 18 In addition, due to vascular system disorders, renin-angiotensin damages the ganglion cell layer, the nerve fiber layer. 19 In the post-transplant stage, optic nerve atrophy is thought to be associated with post-transplant infection.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Diagnosis of optic nerve atrophy was observed with a C/D ratio >0.6, and OCT optical tomography showed a decrease in the retinal nerve fiber layer < 85 μm. 9 The epiretinal membrane is diagnosed when a macular wrinkle is seen, and an OCT scan shows a membrane. Criteria for diagnosing dry eyes are the Schirmer Test < 10mm, the BUT< test 10 seconds, and OSDI > 10 points.…”
Section: Methodsmentioning
confidence: 99%
“…For example, patients with iron deficiency anemia (IDA) were reported to have significantly thinner peripapillary retinal nerve fiber layer (RNFL) thickness, and the Hgb levels were also significantly correlated with the average RNFL thickness value ( Türkyilmaz et al, 2013 ; Akdogan et al, 2015 ). Additionally, optic atrophy, disc edema, and epiretinal tissue on the optic disc have been identified in anemia patients ( Sethi et al, 2020 ; Ab Gani et al, 2021 ; Graf et al, 2021 ), which suggested that the optic disc was susceptible to be affected by anemia. Moreover, ASModel_UWF paid attention to the peripheral retina.…”
Section: Discussionmentioning
confidence: 99%